Clay mineralogy and geochemistry of the Lower Pleistocene Loess in the Iranian Loess Plateau (Agh Band section) and implications for its provenance and paleoclimate change. (30th June 2020) - Taheri, Mehdi; Khormali, Farhad; Wang, Xin; Amini, Arash; Landi, Ahmad; Wei, Haitao; Kehl, Martin; Chen, Fahu
Abstract: The clay mineralogy and geochemistry of loess is sensitive to variations in sediment source area, transport processes and weathering regime over time, and thus careful study of them can provide some insight into past climate variability. The well-known loess–paleosol sequences (Upper Pleistocene Loess (UPL)) on the Iranian Loess plateau (ILP) are generally underlain by the red deposits consisting of reddish clay to silt-sized sediments of wind-blown origin (Lower Pleistocene Loess (LPL)). Study and analyzing of this oldest brown and reddish brown loess has a specific role in paleoclimate reconstruction but no previous study of the clay mineralogical and geochemical characteristics of them has been performed to date. Therefore, total (Fet ) and free iron (Fed ) concentrations and Fed /Fet ratios, X-ray diffraction as well as geochemical analysis were carried out on a section near the Agh Band village in northeastern province Golestan. Geochemical analysis revealed the same provenance of all deposits in LPL and similarity of them by UPL. X-ray diffraction detected the kaolinite, smectite, chlorite, illite, vermiculite, mica-vermiculite and mica-smectite minerals in the red deposits. The results demonstrated that detrital input is the main source of kaolinite, chlorite and illite, while pedogenic formation during the early Pleistocene could be the dominant cause of smectite and vermiculite occurrences in the LPL. The presence of smectite and vermiculite is in accordance with the xeric and udic soil moisture regime in UPL, respectively. As such it can be concluded that the climate at the time of Agh Band LPL formation varied from semi-arid to sub-humid climate and wetter and more favorable conditions than the overlying late Pleistocene loess and modern soils. These results are confirmed by Al2 O3 /Na2 O, Na2 O/K2 O, MgO/TiO2 and Fed /Fet ratios. Highlights: The clay mineralogy and geochemistry of Lower Pleistocene loess was studied. Smectite, chlorite, illite, vermiculite, mica-vermiculite and mica-smectite minerals were detected in the red deposits. The presence of smectite and vermiculite is in accordance with the xeric and udic soil moisture regime. Clay minerals could be acceptable proxy to deduce paleoclimate.